Enhanced Efficacy of Photodynamic Therapy via a Sequential Targeting Protocol - Kessel, David (2014)
This study was designed to examine determinants of the discovery that low-dose lysosomal photodamage (lyso-PDT) could potentiate the efficacy of subsequent low-dose mitochondrial photodamage (mito-PDT). The chlorin NPe6 and the benzoporphyrin BPD were used to separately target lysosomes and mitochondria, respectively, in murine hepatoma cells. Lyso-PDT (LD(5) conditions) followed by mito-PDT (LD(15) conditions) enhanced the loss of the mitochondrial membrane potential, activation of procaspases-3/7 and photokilling. Reversing the sequence was less effective. The optimal sequence did not enhance reactive oxygen species formation above that obtained with low-dose mito-PDT. In contrast, alkalinization of lysosomes with bafilomycin also enhanced low-dose mito-PDT photokilling, but via a different pathway. This involves redistribution of iron from lysosomes to mitochondria leading to enhanced hydroxyl radical formation, effects not observed after the sequential procedure. Moreover, Ru360, an inhibitor of mitochondrial calcium and iron uptake, partially suppressed the ability of Bafilomycin to enhance mito-PDT photokilling without affecting the enhanced efficacy of the sequential protocol. We conclude that sequential PDT protocol promotes PDT efficacy by a process not involving iron translocation, but via promotion of the pro-apoptotic signal that derives from mitochondrial photodamage.